Determinants of Consumers' Choice of Islamic Financing Products - Mohd Abbas, Samsuwatd Zuha (2003)
The Islamic banking has been in Malaysia since the set up of the first Islamic bank on 1st March 1983. Ten years later, the Malaysian government launched the Interest Free Banking Scheme (SPTF), which later renamed Islamic Banking Scheme (SPI). Today, the consumers' acceptance toward the Islamic banking system especially the financing section is still below the target set by the government. In analyzing why the consumers' are not taking Islamic financing, the study had focus to factors that determine consumers' choice. Studies that had been conducted were on the factors that influence customers' selection for a bank is directly related to the factors determining consumers' choice. The researchers identified various factors such as the quality of bank products and services, existence of branches, friendliness or customers' relation, availability of credit, friend's recommendation, location, speed of processing, uncertainty of return and risk involved, customers' awareness, publicity of products and availability of products.Therefore the main objective of the study is to determine factors that determine consumers' choice in selecting Islamic financing products introduced by the commercial banks. In order to determine the choice, the study will analyse the reasons that determine consumers' choice toward Islamic financing products. The reasons were derived from the literatures and interviews conducted with the bankers. A set of questionnaire was designed and distributed to the public. A total of 269 completed questionnaires were returned from 500 questionnaires distributed. In analyzing the results of the research various methods had been used. Among them were the Pearson Correlation, factor analysis and regression analysis. The Pearson Correlation is used to determine the relationship among the variables that determine customers' choice, to measure the strength of association between two variables and determine the degree to which the variables are related. The factor analysis was used to determine the reasons that influence their choice toward Islamic financing products and reduce the 24 reasons (variables) into 6 factors. The 6 factors comprised of Factor 1 "staff", Factor 2 "application process", Factor 3 "customer awareness and knowledge", Factor 4 "customer preference", Factor 5 "risk and return", and Factor 6 "products offering". The factor analysis results indicate that the staff factor such as inefficient, unfriendly, unknowledgeable staff is the main contributors that determine consumers' choice toward Islamic financing. The staff factor contributes 30.044% as compared to other factors that are less than 12.0%. Lastly the discriminant analysis is used to determine the relationship that best distinguish (discriminate) between choosing Islamic financing and conventional financing with the factors determining customers' choice. The discriminant analysis results show that Factor 4 Customer's Preference has the highest positive standardized coefficient of 0.667 followed by Factor 2 Application Process 0.381 and Factor 3 Customer's Awareness and Knowledge 0.331. This means that all the three factors had greater contribution in discriminating the groups between Islamic financing products and conventional financing products